The moral position of chastity in Surah Noor with emphasis on the interpretive opinions of Ayatollah Javadi Amoli - Soheila hassanzadeh; Alireza Alebouyeh (اخلاق وحیانی, 2024)
AbstractChastity is one of the moral concepts that, although it is discussed in the Greek philosophical ethics as one of the four virtues, it has a special place in the system of values of religious ethics. The Qur'an pays special attention to the issue of chastity and its role in personal and social health, and it has been specifically addressed in some surahs, including Surah Noor. By examining the place of chastity in Surah Noor, it can be seen that God has mentioned individual and social chastity and the means of obtaining it in connected and related verses.Types of chastity cover different aspects of human life and men and women are called to observe chastity and self-restraint both in their looks and in their speech. Also, the strategies to spread this moral virtue in the society can be used from the verses of Surah Noor.After stating the types of chastity in Surah Noor about chastity, the present research has analyzed them in a descriptive-analytical way and by using library data and interpretation method, especially the interpretation opinions of Ayatollah Javadi Amoli. From the conducted investigations, it is concluded that according to Ayatollah Javadi-Amoli, chastity is a sensual state that prevents lust from overpowering a person and is also used in instinctive and financial matters. and practical solutions in learning and spreading chastity; Trying to refine the self is to hide the sexual relations of spouses, to promote the culture of marriage and to have the ability to control sensual desires.